EFFECTS OF ALKALINE SANDY LOAM ON SULFURIC SOIL ACIDITY AND SULFIDIC SOIL OXIDATION - Michael, Patrick S. (International Journal of Environment, 2015)
In poor soils, addition of alkaline sandy loam containing an adequate proportion of sand, silt and clay would add value by improving the texture, structure and organic matter (OM) for general use of the soils. In acid sulfate soils (ASS), addition of alkaline sandy would improve the texture and leach out salts as well as add a sufficient proportion of OM for vegetation establishment. In this study, addition of alkaline sandy loam into sulfuric soil effectively increased the pH, lowered the redox and reduced the sulfate content, the magnitude of the effects dependent on moisture content. Addition of alkaline sandy loam in combination with OM was highly effective than the effects of the lone alkaline sandy loam. When alkaline sandy was added alone or in combination with OM into sulfidic soil, the effects on pH and the redox were similar as in the sulfuric soil but the effect on sulfate content was variable. The effects under aerobic conditions were higher than under anaerobic conditions. The findings of this study have important implications for the general management of ASS where lime availability is a concern and its application is limited. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 42-54